The Educational Supervision Situation in Kindergartens and its developinitsg Trends from the Point of view of the Teachers and educational Supervisors (A Real Study in Damascus Province) - al-moukatren, suzan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present research aims to recognize the educational supervision situation in the Syrian Arab Republic through knowing its aims, methods , missions and the difficulties that limit its affectivity . It also shows some contemporary trends of educational supervision . To achieve these aims , a questionare was prepared to see the educational supervision situation . The most important points in this questionnaire were : The educational supervision aims , its ways methods , missions, and problems . The researcher used the analytical descriptive method , where a questionnaire consists of 40 points were applied on 139 teachers and 31 educational supervisors . The results showed : 1 – There are no differences of statistic denotation among the teachers and supervisors in the aims and methods of the educational supervision . 2 – There are differences of statistic denotation among teachers opinions and supervisors in the difficulties which limit the supervisal affectivity. مشكلاته"، استخدمت الباحثة المنهج الوصفي التحليلي، حيث تم إعداد استبانة مؤلفة من (40) بنداً، طبقت على عينة بلغت (139) معلم ومعلمة و(31) مشرفة تربوية. أظهرت النتائج : 1- عـدم وجود فروق ذات دلالة إحصائية بين عينة المعلمات والمشرفات فـي كل من أهدف وأساليب ومجالات الإشراف التربوي. 2- وجود فروق ذات دلالة إحصائية بين أراء المعلمات والمشرفات في المعوقات التي تحد من فاعلية الإشراف التربوي. The present research aims to recognize the educational supervision situation in the Syrian Arab Republic through knowing its aims, methods , missions and the difficulties that limit its affectivity . It also shows some contemporary trends of educational supervision . To achieve these aims , a questionare was prepared to see the educational supervision situation . The most important points in this questionnaire were : The educational supervision aims , its ways methods , missions, and problems . The researcher used the analytical descriptive method , where a questionnaire consists of 40 points were applied on 139 teachers and 31 educational supervisors . The results showed : 1 – There are no differences of statistic denotation among the teachers and supervisors in the aims and methods of the educational supervision . 2 – There are differences of statistic denotation among teachers opinions and supervisors in the difficulties which limit the supervisal affectivity.